Feline Panleukopenia Virus With G299E Substitution in the VP2 Protein First Identified From a Captive Giant Panda in China - Yi, Shushuai; Liu, Songrui; Meng, Xianyong; Huang, Pei; Cao, Zengguo; Jin, Hongli; Wang, Jianzhong; Hu, Guixue; Lan, Jingchao; Zhang, Dongsheng; Gao, Yuwei; Wang, Hualei; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
A feline panleukopenia virus (FPV), Giant panda/CD/2018, was isolated from a captive giant panda with mild diarrhea in 2018 in Chengdu, China, and further identified via indirect immunofluorescence assay (IFA), transmission electron microscopy (TEM) observation, and genetic analysis. Phylogenetic analysis based on the complete VP2 nucleotide sequences showed that it shared high homology with Chinese FPV isolates and grouped within FPV cluster 1. One unique substitution Gly(G)299Glu(E) in the capsid protein VP2 was first identified with Giant panda/CD/2018. The presence of the G299E substitution is notable as it is located on the top region of the interconnecting surface loop 3, which may be involved in controlling the host range and antigenicity of FPV. These findings first demonstrate that FPV with natural point mutation G299E in the VP2 gene is prevalent in giant panda and suggest that etiological surveillance and vaccination among all giant pandas are urgently needed to protect this endangered species against FPV infection.